2021
DOI: 10.1097/coh.0000000000000703
|View full text |Cite
|
Sign up to set email alerts
|

Renal adverse drug reactions

Abstract: Purpose of review Chronic kidney disease (CKD) is common in people living with HIV (PLWH) and is related to a multitude of factors. The aim of this review is to provide an overview of the most recent evidence of renal adverse effects of antiretroviral drugs, predictors of CKD risk and areas for future research. Recent findingsAdvancing age, cardiometabolic risk factors and adverse effects of antiretroviral drugs contribute to the higher prevalence of CKD in PLWH. Genetic factors and baseline clinical CKD risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Indeed, in the stratified analyses, we found particularly elevated SMRs among 'early testers' who, conversely, almost certainly underwent HAART and could have been affected by the nephrotoxic effects of antiviral treatments. 26 Our findings reflect the increased incidence of kidney diseases among HIV-infected people compared with non-HIV-infected. 17 An observational nationwide French study reported a 1.5-fold higher prevalence of kidney diseases among hospitalised people with HIV than in the general population, with an increasing trend over time.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Indeed, in the stratified analyses, we found particularly elevated SMRs among 'early testers' who, conversely, almost certainly underwent HAART and could have been affected by the nephrotoxic effects of antiviral treatments. 26 Our findings reflect the increased incidence of kidney diseases among HIV-infected people compared with non-HIV-infected. 17 An observational nationwide French study reported a 1.5-fold higher prevalence of kidney diseases among hospitalised people with HIV than in the general population, with an increasing trend over time.…”
Section: Discussionsupporting
confidence: 54%
“…However, our cohort of PWA mostly consisted of people with a short time interval between the first HIV-positive test and AIDS diagnosis (ie, late testers) who, probably, had never been treated with HAART. Indeed, in the stratified analyses, we found particularly elevated SMRs among ‘early testers’ who, conversely, almost certainly underwent HAART and could have been affected by the nephrotoxic effects of antiviral treatments 26…”
Section: Discussionmentioning
confidence: 79%
“…Finally, a newer formation of tenofovir (tenofovir alafenamide) might be less nephrotoxic than TDF in the short term, although longer term benefits are unclear, and the active ingredient is the same. 49 …”
Section: Discussionmentioning
confidence: 99%
“…Clinical use of TDF has generally been well tolerated, however TDF regimens are associated with renal adverse events and bone abnormalities (Nelson et al, 2007). The renal events linked to TDF therapy include acute kidney injury, proximal tubular dysfunction, and chronic kidney disease (Hughes, 2021). Concomitant risk factors for renal events linked to TDF therapy have been identified, and it is recommended that clinicians monitor such patients closely.…”
Section: Introductionmentioning
confidence: 99%